OGC P12 Maintaining high volume oesophagagogastric resections during the COVID-19 pandemic: a single centres experience utilising the independent sector. (7th December 2022) - Youssef, Fady; Jackson, Andrew; Virely-Carr, Harriet; Hossain, Tanvir; Yanni, Fady; Trotter, Martin; Zanotti, Daniela; Catton, James; Welch, Neil; Humes, David; Vohra, Ravi; Parsons, Simon L
Abstract: Background: With many resources redirected to care for the those affected by the COVID-19 pandemic, the NHS faced unprecedented pressure to maintain oesophagogastric (OG) cancer resectional services. Our institution along with many tertiary units across the country were faced with limited access to essential critical care beds. The implementation of emergency contracts between the NHS and the independent sector (IS) allowed our unit to maintain a high volume resectional service by utilising the resources of a local private hospital with HDU/ ITU provision. We began operating within the IS shortly after the first UK lockdown in March 2020, and continued through till February 2022. During this period, we continued operating at our tertiary unit (TU) albeit at a reduced capacity. This study aimed to evaluate the surgical outcomes of patients undergoing major OG resectional surgery between the two sites. Methods: This retrospective study included all patients who underwent major OG resectional surgery (including GIST) from March 2020-February 2022. Operation type and site were identified using OPCS-4 clinical codes and combined with National OG Cancer Audit (NOGCA) data to compare basic patient demographics, length of stay, complication rates, COVID infection rates and 90-day mortality. Descriptive and statistical analysis between the two operating sites was performed. Results: A total of 204 major OG resections were undertaken, 44% (89) at our TU;57 oesophagectomies and 32 gastrectomies, with 56% (115) at a local IS hospital;86 oesophagectomies and 29 gastrectomies. Additionally, 13 (6.4%) open and close procedures were performed across both sites. Median patient age was similar, 69 (45–86) years at our TU v. 68 (38–85) years at the IS site. A higher proportion of ASA 3 patients (46%) were operated on at our TU. No difference in median length of stay was observed; TU= 8 (1–93) days v. IS =9 (3–69) days, this included all patients who were repatriated to the TU. Higher complication rates seemed to occur in patients operated at the IS site v. the TU though these did not reach statistical significance; 18 (15.7%) patients suffered an anastomotic leak v. 9 (10.1%) respectively (p= 0.246). 21 (18.3%) v. 13 (14.6%) patients suffered a major respiratory (p=0.487) and 4 (3.5%) v. 1 (1.1%) a major cardiac (p=0.281) complication. There were no cases of COVID infection within 30 days of primary procedure at the IS site, with 2 cases within the TU cohort. Our 90-day mortality rates were similar (IS= 4.54% v. TU=5.32%), p=0.661. Conclusions: Our study demonstrates that resection of patients with OG cancer is feasible in an independent sector hospital if supported by critical care. It allowed a high-volume tertiary unit to continue offering potentially curative surgery to patients whose treatment options would have otherwise been limited to oncological therapy only. Long term survival data compared to non-resecting trusts is required to determine whether this approach was superior. When considering future pandemic planning, we have demonstrated the value of this model in maintaining major OG resectional services.